Great Transition in India: A Multidisciplinary Perspective - CHANWAHN KIM; RAJIV KUMAR (The Journal of Indian and Asian Studies)
This special issue is part of an ongoing project by the Institute of Indian Studies at Hankuk University of Foreign Studies, titled Great Transitions in India: A Korean Perspective on Indian Studies. Launched in 2017 with the support of a significant research grant from the National Research Foundation of Korea (NRF) under the prestigious Humanities Korea Plus (HK[Formula: see text]) program, the project aims to explore India’s major transformations from a multidisciplinary viewpoint. Building on the momentum of the Journal of Indian and Asian Studies (JIAS) special issue series introduced in 2021, which focused on key changes in India, this issue continues that exploration. It brings fresh insights by integrating perspectives from the humanities and social sciences. This special issue is the result of an international conference on Great Transitions in India, held in May 2024 at the Institute of Indian Studies, Hankuk University of Foreign Studies, Seoul. The conference gathered scholars from various disciplines, each contributing to a broader understanding of India’s profound changes. By offering a multidisciplinary perspective, this issue seeks to advance the current body of literature and encourage scholars of Indian and South Asian studies to adopt cross-disciplinary approaches, fostering deeper insights into India’s transformations.